Effects of maturity at harvest on the nutritive value and ruminal digestion of Eragrostis tef (cv. Moxie) when fed to beef cattle1. (18th May 2018) - Vinyard, James R; Hall, John B; Sprinkle, James E; Chibisa, Gwinyai E
Abstract: Teff ( Eragrostis tef cv. Moxie), a warm-season annual grass, could be an excellent forage for beef cattle. However, there is limited information on its nutritive value to cattle when harvested at different stages of maturity. Thus, the objective of this research was to determine the effect of feeding teff hay harvested at the boot (BT ), early-heading (EH ), or late-heading (LH ) stages of maturity on nutrient intake, ruminal fermentation characteristics, omasal nutrient flow, and N utilization in beef cattle. Six ruminally cannulated beef heifers (mean initial BW ± SD, 476 ± 32.6) were used in a replicated 3 × 3 Latin square design with 28-d periods (18 d for adaptation and 10 d for measurements). Dry matter intake was measured daily. Indwelling pH loggers were used to measure ruminal pH from days 21 to 28. Ruminal fluid and omasal digesta were collected from days 26 to 28 to determine fermentation characteristics and omasal nutrient flow. Fecal and urine samples to quantify N excretion were also collected (days 26 to 28). Blood samples for plasma urea-N (PUN ) determination were collected 3 h post-feeding on day 28. There were no changes ( P > 0.28) in the ADF or NDF content of teff with advancing maturity, but indigestible NDF increased ( P < 0.01) with increasing maturity. Maturity had no effect ( P ≥ 0.14) on DMI, and ruminal total short-chain fatty acid (SCFA ) concentration, pH, digestibility, and outflow of DM, OM, NDF, ADF, and CP. However, the CP content of BT hay was greater ( P < 0.01) than for EH and LH hay (18.1, 14.1, and 11.5%, respectively, DM basis), and this resulted in the higher CP intake ( P < 0.01) for heifers fed the BT than the EH and LH hay. Consequently, ruminal ammonia-N (NH 3 -N ) concentration was greater ( P < 0.01) for heifers fed BT than EH and LH hay, thereby possibly explaining the tendency for a decrease ( P = 0.08) in PUN concentration, and a decrease ( P < 0.01) in the excretion of total N, urine N, and urea-N (UUN ) with advancing maturity. However, fecal N excretion (g/d) did not differ ( P = 0.76). In conclusion, despite a decrease in CP intake and ruminal NH3 -N concentration, feeding beef heifers EH and LH compared to BT teff hay did not compromise ruminal digestion and outflow of DM, OM, NDF, ADF, and CP, and microbial protein synthesis. Advancing maturity in teff hay also resulted in a decrease in the excretion of total N and urine N and UUN when fed to cattle.